The Failure of Term Limits in Florida - Depalo, Kathryn A. (Book collections on Project MUSE., 2015)
Proponents of term limits have constantly argued that term limits of its legislature created more honest and creative legislative body, but DePalo's twenty-year study of term limits in Florida shows this is not the case, finding that term limits create a more powerful governor, legislative staffers, and lobbyists.